The marketing program is in general marketing management on aeronautical industrial enterprises - Корж, М. В. (Proceedings of National Aviation University (archive), 2013)
In the article the offered is methodology of development of the marketing program and mechanism of realization of the marketing planning, by the use of approach of the systems, and also its adaptation is conducted for aeronautical industrial enterprises taking into account their features of functioning in the modern terms of economic development of Ukraine. In connection with that the model of organization of management marketing activity is developed on a modern industrial enterprise which carries out the production of goods.